Manipulating Protein Degradability in the Rumen to Support Higher Ruminant Production - Haryanto, Budi (Indonesian Bulletin of Animal and Veterinary Sciences, 2014)
Dietary protein is digested to a certain extent in the rumen causing decreases its potency as source of amino acids for the animal. Dietary protein should mostly reach the intestines where the protein digestion takes place and absorption occurs in the form of intact amino acids and subsequently becomes nutrient deposition in muscles or milk. The higher muscle or milk protein synthesis, the higher the protein in the products of animal, as long as energy for the metabolism is available. Strategies of feeding rumen degradable versus undegradable protein in ruminant have become a research interest for decades. Technologies of dietary protein protection to reduce its degradability in the rumen by heating, chelating or coating have been developed. Key words: Protein, degradability, protection, rumen